FieSta - an approach for fine-grained scope definition, configuration and derivation of model-driven software product lines (2009)
"We present FieSta, an approach based on Model-Driven Development ideas to create Software Lines (SPLs). In Model-Driven SPL approaches, the derivation of a product starts from a domain application model. This model is transformed through several stages reusing model transformation rules until a product is obtained. Transformations rules are selected according to variants included in configurations created by product designers. Configurations include variants from variation points, which are relevant characteristics representing the variability of variability of a product line. FieSta (1) provides mechanisms to improvide the expression of variability of model-driven SPLs by allowing designers to create fine-grained configurations of products, and (2) integrates a product derivation process which uses decision models and Aspect-Oriented Programming facilitating the reuse, adaptation and composition of model transformation rules ..."